Media Pembelajaran Fisika Berbasis Mobile Learning pada Platform Android Menggunakan Aplikasi App Inventor untuk Meningkatkan Kemandirian Belajar Peserta Didik - syaputrizal, nelsi; jannah, raudhatul (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2019)
This research is motivated by the need for learning media that can be used anytime and anywhere in increasing students' independence, so design learning media in the form of mobile learning-based learning media on the android platform. This study aims to (1) to develop mobile learning-based physics learning media on the android platform using the App Inventor application, (2) to produce physics learning media based on mobile learning on the android platform using the App Inventor application to improve student learning independence which is valid, practical and effective. This research uses the research and development (R & D) type of research and development, with a 4-D model starting from defining, designing, developing and disseminate stages. Media learning based on mobile learning on the android platform tested its validity by 1 linguist, 2 material experts, 2 media experts, tested practicality by 2 physics educators and 20 students and tested the effectiveness of 39 students. The instrument used was a questionnaire using a Likert Scale. The results showed that (1) the physics learning media based on mobile learning on the android platform was very valid according to 5 validators with an average value of 92.12%. (2) physics learning media based on mobile learning on the android platform is very practical in terms of content, presentation, benefits, and opportunities for the use of instructional media according to 2 physics educators with an average value of 81.25% while according to 20 students of class XI with the acquisition of scores on average 85.25% and (3) physics learning media based on mobile learning on the android platform are effectively used according to 39 students of class XI with an average value of 83.01%. Based on the results of data acquisition shows that the physics learning media based on mobile learning on the android platform can improve the learning independence of students with very valid criteria, very practical and very effective to use in XI class physics learning.